Answer:
Hi there!
The correct answer is: (x+8)² = 73
Explanation:
First you want to modify the equation: x² + 16x - 6 = 3 into x² + 16x = 9 by adding 6 on both sides.
Then you analyze the new equation, if you can see, 16x is positive which means two positive numbers have to be added up to equal a positive. Which eliminates the choices that have (x-8)²
And now you are left with two choices:
(x+8)² =73 and (x+8)² = -55
Now remember, when you factor out (x+8)² it equals to x² + 16x + 64
next let's bring it back to the very first equation: x² + 16x = 9
now which choice matches the result x² + 16x = 9. The answer will be (x+8)² = 73 because when you subtract 64 on both sides you get 9.